Therapeutic efficacy and safety of tocilizumab in COVID-19. A narrative review (Actualizaciones en Sida e Infectología, 2022)
Up until now, other than corticosteroids, no other pharmacological treatment has shown a decrease in mortality rate in patients with severe-critical COVID-19. In order to discuss its place in therapy, a review and critical reading of the most significant published studies on the use of tocilizumab was carried out.Search was done in the main bibliographic databases, prioritizing the inclusion of systematic reviews and randomized controlled clinical trials (RCTs); that analyzed the effect of tocilizumab on COVID-19 at different endpoints.5 RCTs and 4 meta-analysis were considered in the evaluation, all of them including patients with confirmed COVID-19 and predominantly severe-critical illness. The primary endpoint was 28-day all-cause mortality and, as a secondary outcome of relevance, progression to invasive mechanical ventilation. The safety of the intervention was also analyzed, mainly the occurrence of secondary infections.From our analysis it appears that the greatest possibility of benefit seems to be limited to patients with severe-critical illness, who receive corticosteroids, with high markers of inflammation values (CRP> 10 mg/dL) and rapidly progressive disease. There is high certainty regarding the impact of tocilizumab in preventing progression to IMV, with a small effect size and moderate certainty regarding its impact on mortality. Moreover, it was a well-tolerated and safe medication.
Keywords: tocilizumab; COVID-19; treatment